Specification for solid rivets with universal head made from BS L 86 (SP 157 and 163), BS L 58 (SP 160 and 161), BS L 37 (SP 162) and DTD 204 (SP 158 and 159) materials. (30th November 1973) - British Standards Institution
No abstract available